Genomic Porosity between Invasive Chondrostoma nasus and Endangered Endemic Parachondrostoma toxostoma (Cyprinidae): The Evolution of MHC IIB Genes - Simková, Andrea; Civáňová, Kristína; Gettová, Lenka; Gilles, André (PloS one, 2013)
Two cyprinid species, Parachondrostoma toxostoma, an endemic threatened species, and Chondrostoma nasus, an invasive species, live in sympatry in southern France and form two sympatric zones where the presence of intergeneric hybrids is reported. To estimate the potential threat to endemic species linked to the introduction of invasive species, we focused on the DAB genes (functional MHC IIB genes) because of their adaptive significance and role in parasite resistance. More specifically, we investigated (1) the variability of MHC IIB genes, (2) the selection pattern shaping MHC polymorphism, and (3) the extent to which trans-species evolution and intergeneric hybridization affect MHC polymorphism. In sympatric areas, the native species has more diversified MHC IIB genes when compared to the invasive species, probably resulting from the different origins and dispersal of both species. A similar level of MHC polymorphism was found at population level in both species, suggesting similar mechanisms generating MHC diversity. In contrast, a higher number of DAB-like alleles per specimen were found in invasive species. Invasive species tended to express the alleles of two DAB lineages, whilst native species tended to express the alleles of only the DAB3 lineage. Hybrids have a pattern of MHC expression intermediate between both species. Whilst positive selection acting on peptide binding sites (PBS) was demonstrated in both species, a slightly higher number of positively selected sites were identified in C. nasus, which could result from parasite-mediated selection. Bayesian clustering analysis revealed a similar pattern of structuring for the genetic variation when using microsatellites or the MHC approach. We confirmed the importance of trans-species evolution for MHC polymorphism. In addition, we demonstrated bidirectional gene flow for MHC IIB genes in sympatric areas. The positive significant correlation between MHC and microsatellites suggests that demographic factors may contribute to MHC variation on a short time scale.
Keywords: rekombinace genetická; alely; molekulární evoluce; Phylogeny; Recombination, Genetic; polymorfismus genetický; Evolution, Molecular; Alleles; zvířata; geny MHC třídy II; Polymorphism, Genetic; Endangered Species; fylogeneze; zavlečené druhy; Bayesova věta; Genes, MHC Class II; ohrožené druhy; Animals; Introduced Species; Bayes Theorem; Cyprinidae